Analisis Karakteristik Sensori, Zat Gizi, dan Aktivitas Antioksidan Es Krim Rendah Lemak Substitusi Sari Buah Belimbing Wuluh (Averrhoa Bilimbi L) - Darma Septiani, Miranti; Amrinanto, Ahmad Hisbullah; Muh. Guntur Sunarjono Putra (Program Studi Teknik Kimia, Universitas Pamulang, 2025)
Rising global obesity rates demand the development of low-calorie food options. This study explores the potential of starfruit, a fruit low in fat and energy, as a substitute ingredient in ice cream. Using a Completely Randomized Design (CRD) with three different formulas (F1, F2, F3) based on starfruit juice concentration, the research analyzed the sensory, nutritional, and antioxidant characteristics of the final product. The sensory test results showed significant differences in color and aftertaste attributes, with formula F1 (20 grams of starfruit juice) selected as the best. Per 100 grams, the F1 ice cream has a low nutritional content: 126 kcal of energy, 4.2 g of protein, 2.6 g of fat, and 21.6 g of carbohydrates. The nutritional contribution per serving is well below the Daily Reference Values (DRV), making it an effective low-calorie food choice. However, its antioxidant activity is very weak, with an IC50 of 8275 ppm. Overall, starfruit-substituted ice cream offers an innovative solution for low-calorie foods.